2017
DOI: 10.1039/c7ra02204b
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted synthesis of cobalt sulphide nanoparticle clusters on activated graphene foam for electrochemical supercapacitors

Abstract: Microwave-assisted synthesis of cobalt sulphide (Co9S8) nanoparticles clusters on activated graphene foam (AGF) with high specific capacitance of 1150 F g−1 at a scan rate of 5 mV s−1 as an electrode (Co9S8/AGF) for electrochemical supercapacitor applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…As for CoS2, the change of atmosphere from H2S to N2 leads on the spectrum of Co9S8 to a shift of these lines to 392 and 332 cm -1 (Figure S8 (b)). To the best of our knowledge, among dozens of papers [19][20][21][22][23] where lines mostly located above 500 cm -1 were attributed to Co9S8, only one [17] reported recently similar line positions to the ones published herein for bulk Co9S8, with a small shift which could be ascribed to the atmosphere at which measurements were carried out (unfortunately not specify in [17]).…”
Section: Raman Characterization Of Bulk Co9s8mentioning
confidence: 72%
See 2 more Smart Citations
“…As for CoS2, the change of atmosphere from H2S to N2 leads on the spectrum of Co9S8 to a shift of these lines to 392 and 332 cm -1 (Figure S8 (b)). To the best of our knowledge, among dozens of papers [19][20][21][22][23] where lines mostly located above 500 cm -1 were attributed to Co9S8, only one [17] reported recently similar line positions to the ones published herein for bulk Co9S8, with a small shift which could be ascribed to the atmosphere at which measurements were carried out (unfortunately not specify in [17]).…”
Section: Raman Characterization Of Bulk Co9s8mentioning
confidence: 72%
“…But the atmosphere dependence of the line position is not responsible for the inconsistency of published results in the abundant literature related to electrocatalysts because the lines used in those papers are shifted by several hundreds of cm -1 compared to our positions. The formation of Co9S8 is concluded from the presence of a main line at 573 [23], 586 [20], 650 [19], 667 [21] or 685 cm -1 [22] to cite only a few of these papers. We ascribe that those lines arise from laser radiation damage, since we have experienced by ourselves the high sensitivity of bulk Co9S8 under air when the laser power was increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over other traditional synthetic approaches, the microwave route has the advantages of the super-rapid and uniform process in the preparation of nanomaterials such as nanoparticles, metal–organic frameworks, graphene oxide, and nanowires due to its dielectric heating. The benefits of the route contribute to setting aside an army of time and energy sources, and providing a low-cost and highly efficient synthesis process.…”
Section: Introductionmentioning
confidence: 99%
“…Later Ramachandran et al [ 122 ] suggested a low cost synthetic route for Co 9 S 8 nanoflake/graphene composite electrodes that offered a maximum specific capacitance of 808 F·g −1 at 5 mV·s −1 in 6 M KOH electrolyte solution. Mashikwa et al [ 123 ] developed a new type of SC electrode consisting of Co 9 S 8 nanoparticle clusters embedded in an activated graphene foam structure using a microwave-assisted hydrothermal method; the electrode was capable of delivering a specific capacitance of 1150 F·g −1 at 5 mV·s −1 . Furthermore, 3-D petal-like two-mixed metal sulfide-graphene composite electrodes (Co 9 S 8 /rGO/Ni 3 S 2 /Ni foam) fabricated for high-performance SCs exhibited superior capacitive performance with the high capability (2611.9 F·g −1 at 3.9 A·g −1 ), excellent rate capability, and enhanced electrochemical stability with remarkable capacitance retention [ 124 ].…”
Section: Transition Metal Sulfidesmentioning
confidence: 99%